Bare Nouns in Brazilian Portuguese: An experimental study on grinding - Kayron Beviláqua; Suzi Lima; Roberta Pires de Oliveira (Baltic International Yearbook of Cognition, Logic and Communication, 2016)
Much literature has explored the interpretation of the bare singular (BS) in Brazilian Portuguese. Pires de Oliveira and Rothstein (2011) claim that BS nouns are mass because they denote kinds and argue that this explains why only the BS in Brazilian Portuguese can have a non-cardinal interpretation. In this paper, based on an experimental task with Brazilian Portuguese adult speakers, we explore one of their predictions, namely that the ‘volume interpretation’ of the BS cannot be explained as a case of Grinding. Our results show that Grinding and Volume readings of a BS noun are not equivalent (in favor of their hypothesis). We also show that a volume interpretation of a noun is never preferred when a cardinal interpretation is available, but that this can be explained by other lexical and pragmatic factors. We conclude by suggesting that Rothstein’s (in press) distinction between counting and measuring accounts for the fact that non-cardinal readings are not grinding.
Keywords: bare nouns; Brazilian Portuguese; Coercion; Mass/Count; Universal Grinder